Analisis Aktivitas Pertambangan Emas Tanpa Izin dan Dampaknya terhadap Kondisi Sosial Ekonomi Masyarakat di Desa Semedang Kecamatan Kuala Behe Kabupaten Landak - Suwarno, Agus; Subihi Subihi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Illegal gold mining (IGM) remains a common phenomenon in many rural areas of Indonesia, including Semedang Village, Kuala Behe District, Landak Regency. This activity has developed as the primary source of livelihood for local communities amid limited employment opportunities and difficulties in obtaining legal mining permits. On the other hand, it has generated complex social, economic, and environmental impacts on the surrounding community. This study aims to analyze illegal gold mining activities, particularly the partnership arrangements between miners, financiers (toke), and landowners, and to examine the impacts of illegal gold mining on the socio-economic conditions of the community. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, documentation, and literature review involving the village head, gold miners, and landowners selected through purposive sampling. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that illegal gold mining activities in Semedang Village are conducted under an oral profit-sharing agreement based on mutual trust among miners, financiers (toke), and landowners. Illegal gold mining has contributed positively by increasing community income and creating supporting business opportunities. However, it has also resulted in negative impacts, including changes in community lifestyles, declining mutual cooperation, the emergence of social conflicts, and environmental degradation caused by mining activities. These findings indicate that illegal gold mining provides significant economic benefits while simultaneously creating social and environmental challenges that require sustainable management.